2021
DOI: 10.3389/fpsyg.2021.646027
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being of Adolescents in De-Escalation Situation: Physical, Emotional, Social, and Academic Impact

Abstract: The Covid-19 pandemic has changed the world we knew in recent months. In the interest of maintaining social distance, lockdown periods have been established and schools in many countries have closed their doors. In this context, the objective of this research was to analyze the well-being of adolescents in Spain after lock-down and during the de-escalation process in a holistic way; taking into account their indicators on physical, emotional, social, and academic levels. The “Well-being of Children in Lockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Since the WHO declared the global pandemic of COVID-19 in March 2020 [1], in addition to the medical consequences, the psychological and social impact that this pandemic involves is undisputed. As a result, studies on the psychological effects of the pandemic have been conducted worldwide in populations such as health professionals [2], the general population [3], the elderly [4], students [5,6], children [7], adolescents [8], caregivers [9] and teachers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since the WHO declared the global pandemic of COVID-19 in March 2020 [1], in addition to the medical consequences, the psychological and social impact that this pandemic involves is undisputed. As a result, studies on the psychological effects of the pandemic have been conducted worldwide in populations such as health professionals [2], the general population [3], the elderly [4], students [5,6], children [7], adolescents [8], caregivers [9] and teachers [10].…”
Section: Introductionmentioning
confidence: 99%
“…In table 4 there are five authors who are widely used as references, such as; (Berasategi Santxo et al, 2021;Fuentes-García et al, 2020;Gaeta et al, 2021;Hossain et al, 2020;Sundarasen et al, 2020;Tang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from developed countries has revealed that home confinement resulted in increased screen time which is associated with sedentary behavior, snacking, and poor sleep patterns (Ten Velde et al, 2021) which may result in anxiety, exhaustion, emotional disturbance, and stress. The result of another study conducted to analyze the wellbeing of adolescents in Spain revealed intermediate scores in terms of physical activity and emotional and academic domains (Berasategi Santxo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Further impediments are the limited skill set among parents to navigate digital platforms, appropriately trained school staff, and disruption in power supply, internet, and Wi-Fi connections (Nesar et al, 2021). In this scenario, the already unfavorable conditions for adolescents and youth are further aggravated, leading to mental stress, trauma, and, in several cases, social and emotional stigmatization as is evident in some global literature (Shah et al, 2020;Berasategi Santxo et al, 2021). Even among students who have access to and are adept at using digital devices and platforms, there is differential acceptance of e-learning assimilation and learning methodologies (Ray et al, 2022), both leading to suboptimal and compromised teaching-learning processes.…”
Section: Introductionmentioning
confidence: 99%